Spontaneous Activation of Antigen-presenting Cells by Genes Encoding Truncated Homo-Oligomerizing Derivatives of CD40. Issue 2 (February 2017) - Levin, Noam; Pato, Aviad; Cafri, Gal; Eisenberg, Galit; Peretz, Tamar; Margalit, Alon; Lotem, Michal; Gross, Gideon
Abstract : The interaction between the CD40 receptor on antigen-presenting cells (APCs) and its trimeric ligand on CD4 T cells is essential for the initiation and progression of the adaptive immune response. Here we undertook to endow CD40 with the capacity to trigger spontaneous APC activation through ligand-independent oligomerization. To this end we exploited the GCN4 yeast transcriptional activator, which contains a leucine zipper DNA-binding motif that induces homophilic interactions. We incorporated GCN4 variants forming homodimers, trimers, or tetramers at the intracellular domain of human and mouse CD40 and replaced the extracellular portion with peptide-β2 m or other peptide tags. In parallel we examined similarly truncated CD40 monomers lacking a GCN4 motif. The oligomeric products appeared to arrange in high–molecular-weight aggregates and were considerably superior to the monomer in their ability to trigger nuclear factor kB signaling, substantiating the anticipated constitutively active (ca) phenotype. Cumulative results in human and mouse APC lines transfected with caCD40 mRNA revealed spontaneous upregulation of CD80, IL-1β, TNFα, IL-6, and IL-12, which could be further enhanced by caTLR4 mRNA. In mouse bone-marrow–derived dendritic cells caCD40 upregulated CD80, CD86, MHC-II, and IL-12 and in human monocyte–derived dendritic cells it elevated surface CD80, CD83 CD86, CCR7, and HLA-DR. Oligomeric products carrying the peptide-β2 m extracellular portion could support MHC-I presentation of the linked peptide up to 4 days post-mRNA transfection. These findings demonstrate that the expression of a single caCD40 derivative in APCs can exert multiple immunostimulatory effects, offering a new powerful tool in the design of gene-based cancer vaccines.